Modification by isolevuglandins, highly reactive γ-ketoaldehydes, deleteriously alters high-density lipoprotein structure and function - May-Zhang, Linda S. (J Biol Chem, 2018)
Cardiovascular disease risk depends on high-density lipoprotein (HDL) function, not HDL-cholesterol. Isolevuglandins (IsoLGs) are lipid dicarbonyls that react with lysine residues of proteins and phosphatidylethanolamine. IsoLG adducts are elevated in atherosclerosis. The consequences of IsoLG modification of HDL have not been studied. We hypothesized that IsoLG modification of apoA-I deleteriously alters HDL function. We determined the effect of IsoLG on HDL structure–function and whether pentylpyridoxamine (PPM), a dicarbonyl scavenger, can preserve HDL function. IsoLG adducts in HDL derived from patients with familial hypercholesterolemia (n = 10, 233.4 ± 158.3 ng/mg) were found to be significantly higher than in healthy controls (n = 7, 90.1 ± 33.4 pg/mg protein). Further, HDL exposed to myeloperoxidase had elevated IsoLG-lysine adducts (5.7 ng/mg protein) compared with unexposed HDL (0.5 ng/mg protein). Preincubation with PPM reduced IsoLG-lysine adducts by 67%, whereas its inactive analogue pentylpyridoxine did not. The addition of IsoLG produced apoA-I and apoA-II cross-links beginning at 0.3 molar eq of IsoLG/mol of apoA-I (0.3 eq), whereas succinylaldehyde and 4-hydroxynonenal required 10 and 30 eq. IsoLG increased HDL size, generating a subpopulation of 16–23 nm. 1 eq of IsoLG decreased HDL-mediated [(3)H]cholesterol efflux from macrophages via ABCA1, which corresponded to a decrease in HDL–apoA-I exchange from 47.4% to only 24.8%. This suggests that IsoLG inhibits apoA-I from disassociating from HDL to interact with ABCA1. The addition of 0.3 eq of IsoLG ablated HDL's ability to inhibit LPS-stimulated cytokine expression by macrophages and increased IL-1β expression by 3.5-fold. The structural–functional effects were partially rescued with PPM scavenging.